Analisis Faktor yang Berkontribusi terhadap Kejadian Anemia pada Ibu Hamil - Lutfiatul Wulandari Lutfi; Widia Shofa Ilmia (Universitas Islam Jember, 2025)
Anemia is a disorder in which the body does not have enogh sufficient erythrocytes to meet its physiological needs. This need can differ from person to person, depending on a number of factors such as gender, living environment, smoking habits, and stage of pregnancy. Based on the WHO definition, anemia during pregnancy can be recognized by Hb levels of less than 11 grams/dL in the initial and last trimesters of pregnancy, or if it is during the second trimester, below 10.5 gr/dL. This study's objective is to ascertain the elements that lead to cases of anemia experienced by pregnant women at the UPTD Kemuningsari Kidul Health Center. This type of study is an analysis type employing a cross-sectional design survey method. Respondents in this study consisted of 45 pregnant women. This A The research was conducted in the UPTD Kemuningsari Kidul Health Center service area in May 2025. Analysis of data used the chi-square hypothesis test. The outcomes of the statistical analysis showed a p value of 0.040, so p is below 0.05 for age and p 0.030, so p <0.05 for parity status. Thustherefore, it may be said that parity and pregnant women's age status have a substantial impact on the event of anemia at the UPTD Kemuningsari Kidul Health Center.